Functional finance and intergenerational distribution in a Keynesian OLG model - Peter Skott; Soon Ryoo (University of Massachusetts, Department of Economics, 2015)
This paper examines the role of fiscal policy in the long run. We show that (i) dynamic inefficiency in a standard OLG model generates aggregate demand problems in a Keynesian setting, (ii) fiscal policy can be used to achieve full-employment growth, (iii) the required debt ratio is inversely related to both the growth rate and government consumption, and (iv) a simple and distributionally neutral tax scheme can maintain full employment in the face of variations in 'household confidence'.
Keywords: E62; E22; 330; Public debt; Keynesian OLG model; secular stagnation; structural liquidity trap; dynamic efficiency; confidence